Actual trajectory of strategic management development as a science, in the conditions of dynamically developing markets and external challenges - S. A. Draganov (Путеводитель предпринимателя, 2024)
The article considers the current trajectory of strategic management development as a science in the context of dynamically developing markets and external challenges. The use of strategic management tools is crucial in the activities of enterprises, as they provide the basis for identifying, analyzing and responding to external and internal factors and threats. These tools can help companies develop strategies that will allow them to compete effectively in their industry, achieve their goals and stay ahead of their competitors. This article indicates the main areas where strategic management as a science needs to focus its attention, develop research potential, and look for opportunities to implement in the current activities of companies. The methods of analysis of companies’ strategy aimed at identifying, assessing and managing risks that may affect the ability of the organization to achieve its goals, such as SWOT–analysis and ERM, are considered. The methods of forming strategies of economic, industrial and social character to stimulate effective work of the companies’ employees are considered.